Stray Load Losses in Induction Machines - Jimoh, Adisa Abdul-Ganiya (My University, 1986)
Understanding and minimizing loss are the main objectives of seeking solutions to the problems of stray loss in induction machines. This thesis contributes towards this objective by addressing the various problems of stray load loss. These problems include the questions of definition, origin, components, and effects; theoretical and experimental means of evaluation; and loss reduction.
Insights into these problems are achieved through a comprehensive review of the state of the art of the subject. We have established that some commonly used terminologies in the subject area formed major obstacles to progress in definition.
A conceptually simple and general theory of squirrel cage induction machines is presented. The theory results in a set of linear periodic differential equations, which has an infinite number of possible solutions. A suitable solution procedure is developed.
Means for accounting for slot openings and saturation are developed. These have enabled various field waveforms in a practical machine to be generated and analyzed. The analysis produced insights into the interactions of harmonics and how harmonics contribute to stray load losses. Through this, an approximate means of separating a saturated non-sinusoidal waveform of an air gap flux density waveform into its fundamental, saturation, and other space harmonics is developed. An expression for determining the machine torque is derived. This torque expression, the ideas for manipulating and analyzing the field waveforms, and the presented theory are structured into an algorithm, modeling the behaviours of squirrel cage induction machines. The algorithm enabled the torque-speed characteristic of a practical machine to be predicted.
The predicted characteristic is compared with that measured by means of accelerometer. The fact that it compares very well validates the theory and the developed model. The new steady state model has several advantages, including its easy application to the study and the evaluation of stray load losses. A brief study of how harmonics influence the developed torque is also conducted using the new model.
Two theoretical methods are developed for predicting stray load loss at the design, manufacturing, or utilization stage of a machine. These methods, which employ the developed model, are applied to a practical machine.
The predicted stray losses are compared with the measured, and that predicted using the nominal assignation technique. This draws attention to the need for experimental investigation of the subject. Consequently, two experiments, calorimetric method and novel experiment to study inter-bar current problem, are developed. Due to technical and economic problems, however, their implementation are not yet completed.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering